Determination of asymmetric and symmetric dimethylarginines in human plasma by HPLC with electrochemical detection - Kleparnik, Martin; Tomandlova, Marie; Glatz, Zdenek; Tomandl, Josef (Journal of separation science, 2013)
A new HPLC method was developed and validated for the determination of asymmetric and symmetric dimethylarginines and l-arginine in human plasma. After SPE and evaporation of the eluate, the samples were derivatised with an o-phthaldialdehyde reagent containing 3-mercaptopropionic acid. The derivatives formed were analysed by isocratic RP-HPLC with electrochemical detection at +320 mV. The mobile phase consisted of 50 mM phosphate buffer (pH 6.1) containing 10% v/v acetonitrile, the flow rate was 1 mL/min. The retention times of all compounds including monomethylarginine (internal standard) were <24 min. The LODs (S/N 3:1) were 0.012 μM for both dimethylarginines and 0.013 μM for L-arginine; the linearity of the method was from 0.1 to 20 μM for both dimethylarginines and from 1 to 200 μM for L-arginine. Absolute extraction recoveries measured for all analytes ranged from 85 to 88%.
Keywords: elektrochemické techniky; Electrochemical Techniques; arginin; Arginine; Asymmetric dimethylarginine; vysokoúčinná kapalinová chromatografie; Limit of Detection; lidé; Chromatography, High Pressure Liquid; limita detekce; referenční standardy; Reference Standards; Blood Chemical Analysis; HPLC; Symmetric dimethylarginine; biochemická analýza krve; Electrochemical detection; Humans